The Influence of Farmer Group Dynamics on the Implementation of Good Agricultural Practices (GAP) of Red Chili in Sukajaya District, Bogor Regency - Teguh Firman Suryaman; Rina Hermawati; Syariful Mubarok (Electronic Journal of Education, Social Economics and Technology, 2025)
This study analyzes the influence of farmer group dynamics on the application of Good Agricultural Practices (GAP) in the cultivation of red chili in Sukajaya District, Bogor Regency. Red chili is an important commodity that maintains the stability of the national economy which is vulnerable to fluctuations in price and production. Data shows that there has been a decrease in the productivity of red chili in Sukajaya District despite an increase at the regency level, indicating that the application of GAP is not yet optimal. Using a descriptive quantitative approach and multiple linear regression analysis, this study involved 101 respondents from farmer group members. The results showed that the factors that significantly influenced the application of GAP were group task function, group objectives, guidance, group structure, effectiveness, and pressure, with a contribution of 72.2%. Characteristically, the majority of farmers are men (94%), of productive age 36-45 years (34.7%), with elementary school education (38.6%), very experienced in farming (40.6%), and have sufficiently productive land (41.6%). The strategy to increase the dynamics of farmer groups to optimize the implementation of Good Agricultural Practices (GAP) needs to pay attention to these factors, especially the function of group tasks that have the greatest influence, through training, technical guidance, counseling, and routine monitoring.